Penjarangan Awal Tanaman Sengon Jarak Tanam 2m X 2m Agroforestry Sederhana di Widodomartani Ngemplak Sleman Yogyakarta - Agus Prijono; Rawana; Setiaji Heri Saputro (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2025)
The Widodomartani community cultivates some of their land for forest plants, generally sengon (Falcataria moluccana) is liked community because fast growing species and harvested quickly. Generally, the planting pattern used is simple agroforestry, with a planting distance of 2m x 2m. This research aims to determine the growth using agroforestry pattern ,time the first thinning and their plant components . The growth data taken is in the form of height, diameter and plant components. The growth data obtained was t tested. The results research t tested showed that agroforestry pattern is better than monoculture to 3 aged for average height and average diameter before 3 aged but at 3 aged not significant so this is the right time for the first thinning so that when harvesting the results are optimal. The plant components first year include sengon with intercropping of cassava, chili peppers, blue taro, tomatoes, corn, papaya and after first year sengon, blue taro, papaya. The disturbance found was tumor rust caused by Uromycladium tepperianum.